High-electromechanical performance for high-power piezoelectric applications: Fundamental, progress, and perspective. (June 2022) - Chen, Liang; Liu, Hui; Qi, He; Chen, Jun
Abstract: Piezoelectric materials with excellent electromechanical performance are widely used as core components in high-power applications such as ultrasonic transducers, piezoelectric transformers, ceramic filters and sonar systems. A comprehensive review of the fundamental, progress, and perspective of the various types of piezoelectric materials with high-electromechanical performance based on high mechanical quality factor Qm is presented herein, and in particular, the regulation and optimization of electromechanical performance are systematically introduced and summarized. Based on the investigation and summary, two main key issues faced for high-power applications are elaborated: one is the mutually restrictive relationship between Qm and other parameters ( d33, kp and ɛ ), and the other one is the temperature stability of electromechanical parameters. Next, the factors and internal mechanisms that affect Qm regulation and optimization are discussed in detail, and the effective strategies for improving Qm and weakening the mutually restrictive relationship are proposed to obtain high-electromechanical performance. Subsequently, some discussions and perspectives are put forward in detail as suggestions for the development and design of high- Qm piezoelectric materials with excellent comprehensive performance. It is hoped that this review would be helpful for researchers and engineers to understand the origins of high- Qm and related mechanisms, and to design new high-electromechanical performance piezoelectric materials meeting high-power applications.